Satellite techniques for trace gas measurements - LAL, SHYAM; SHEEL, VARUN; PATRA, PRABIR K. (MAUSAM, 2003)
Satellite measurements of atmospheric minor constituents are very useful as they provide frequent global coverage over a long period of time. Due to technical developments measurements of ozone and other related trace gases are becoming possible since the past decade even in the troposphere. Measurements in the infrared and microwave are being utilised with the advent of new technology. Different types of viewing geometries of satellite observations and retrieval algorithms are discussed with examples for temperature and ozone, respectively. Since India is capable of launching satellites, it is suggested that monitoring some of the key pollutants along with meteorological parameters will be important to understand their transport and chemistry in the tropical region using a low inclination orbit satellite.